The Change of Histamine Content in Some Fish-Based Foods During Storage - Meta Mahendradatta (Indonesian Food and Nutrition Progress, 2003)
Traditional fish-based food product becomes more interesting because of its active compound which function as heald and fitness guard.South sulawesi as a coastal area has lot of fishery product.Histamine content can be used as quality indicators for fishes and fish products.Some fish-based foods have been anlyzed for its histamine contens during storage.There were lawa teri, smoked kembung fish, and skipjack burger.These foods represent the different processes for fishery products.Lawa teri is a traditional fish product from south Sulawesi.It is produced by bringing togrther fish fillet with citrus juice or vinegar, then mixed with fried grated coconut.The Storage was carried out at 5Cfor 2 weeks in two defferent packaging, glass and plastic.The results showed that during storege the histamine content incraesed from 1.009 to 23.023 mg/100g.The storage time showed a significant difference (p<0.05) but there was no significantly difference from the type of packaging, and there was no interaction between type of packaging and storage time on histamine content.Smoked kembung fish was analyzed for its histamine content during storage at 5 C for 20 days in plastic packaging with two various conditions, aerobe and vacuum. The results showed that histamine content of raw material decreased after smoking from 7.280 to 7.045 mg/100 g then decreased to 5.185 mg/ 100 g after drying the smoked fish. During 20 days storage at low temperature the histamine content increased under aerobe as well as vacuum condition. There was a significant difference of storage time on histamine content and also the condition of packaging (p<0.05). The interaction between storage time and condition of packaging showed a significantly difference (p<0.05).Skipjack burger was processed through more various steps by using more ingredients such as flour, egg, and spices. Histamine content was analyzed during storage for 4 weeks at 0 C. The histamine content increased from 0.755 to 0.8196 mg/100g during 4 weeks storage. There was significantly difference on histamine content during storage.